Contextual-Based Animation Video Development for Elementary School Students - Syafni Gustina Sari; Zulfa Amrina; Ira Ramayuni Jusar; Randi Ali Zamardi (FKIP - Universitas Riau, 2026)
Learning boredom and the difficulty of understanding abstract mathematical concepts often become challenges in elementary school learning. One effort to overcome this problem is by utilizing learning media that are interactive and relevant to students’ daily experiences. This study aims to develop contextual-based animated video learning media for fifth-grade elementary school students on the topics of Greatest Common Factor (GCF) and Least Common Multiple (LCM). The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were 28 fifth-grade students at SDN 04 IV Koto Aur Malintang. Data were collected through expert validation sheets, learning outcome tests, and student and teacher response questionnaires. The validation results indicate that the developed animated video media is categorized as valid to very valid in terms of content and media design. The implementation results show an improvement in students’ conceptual understanding, indicated by an increase in the average pre-test score from 78.57 to a post-test score of 90.71 with a high N-gain category. In addition, students and teachers responded positively to the use of the media. Therefore, contextual-based animated video media can support more meaningful and engaging mathematics learning in elementary schools.